Dekonstruksi Wacana Patriarki dan Kebungkaman Perempuan dalam Manuskrip Hikayat Darma Tasiyah - Fatkhu Rohmatin (Perpustakaan Nasional RI, 2019)
In the old tradition of Nusantara literature, in this case Malay and Javanese, often represented a model of society that adhered to a patriarchal system. This system puts women at the subordinate level, under the domination of men. This phenomenon was also represented in one of the manuscripts of the National Library of the Republic of Indonesia collection entitled 'Hikayat Darma Tasiyah' with the script code W 124B. This study aims to deconstruct the point of view of reading the script using Derrida's deconstruction approach model, in order to obtain a new meaning which is binary in opposition to the general meaning produced from the point of view of structural readings. With deconstruction reading, the meaning of obedience and silence turns into acts of resistance, mistakes become rebellion, expulsion is precisely like liberation and so on. As a literary work that discusses the patriarchy system, Hikayat Darma Tasiyah is actually able to turn into a destroyer of the patriarchy system itself, only through deconstruction reading.